2022
DOI: 10.1186/s40360-022-00620-3
|View full text |Cite
|
Sign up to set email alerts
|

Cornin protects against cerebral ischemia/reperfusion injury by preventing autophagy via the PI3K/Akt/mTOR pathway

Abstract: Background Ischemia stroke is the leading cause of disability, which is a consequence of vascular occlusion. The purpose of this study is to investigate the effect of cornin which is isolated from the fruit of Verbena officinalis L, against astrocytes autophagy induced by cerebral ischemia/reperfusion (CI/R) injury in vitro and in vivo and its potential mechanism. Methods Cornin at dose of 2.5, 5 and 10 mg/kg were intravenously injected to MCAO rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…119 Cornin is an iridoid glycoside isolated from the fruit of Verbena of ficinalis L. Recent studies have found that cornin can induce angiogenesis through a variety of mechanisms and plays a therapeutic role in cerebral ischemic injury. 120 Xu et al showed that intravenous injection of cornin improved the sensorimotor function of MCAO rats, increased microvessel density, and upregulated the expression of vascular endothelial growth factor (VEGF) and angiopoietin (Ang1)/Tie2. In addition, cornin reduced the BBB permeability.…”
Section: Natural Compounds Regulate the Wnt Signaling Pathway In Ismentioning
confidence: 99%
“…119 Cornin is an iridoid glycoside isolated from the fruit of Verbena of ficinalis L. Recent studies have found that cornin can induce angiogenesis through a variety of mechanisms and plays a therapeutic role in cerebral ischemic injury. 120 Xu et al showed that intravenous injection of cornin improved the sensorimotor function of MCAO rats, increased microvessel density, and upregulated the expression of vascular endothelial growth factor (VEGF) and angiopoietin (Ang1)/Tie2. In addition, cornin reduced the BBB permeability.…”
Section: Natural Compounds Regulate the Wnt Signaling Pathway In Ismentioning
confidence: 99%
“…However, the loss of membrane PS asymmetry is reversible, and if membrane asymmetry is restored, injured cells are then given the ability to recover, and not be engulfed by inflammatory cells [197,[270][271][272]. With the later phase that involves deoxyribonucleic acid (DNA) degradation in the cell [34,40,77,226,[273][274][275], caspase activation plays a prominent role [15,77,194,206,210,273,[276][277][278]. This process of caspase activation and DNA destruction is irreversible [259].…”
Section: Autophagy Apoptosis Pyroptosis and Ferroptosis Involvement I...mentioning
confidence: 99%
“…This process of caspase activation and DNA destruction is irreversible [259]. Limiting apoptotic cell death may minimize memory loss and cognition during both acute and chronic insults [34,93,96,169,172,185,276,279]. This may occur during measures that reduce inflammatory pathways and affect neuronal and oligodendrocyte survival [9,108,132,187,252,276,[279][280][281][282], as well as cognitive performance [25,[283][284][285].…”
Section: Autophagy Apoptosis Pyroptosis and Ferroptosis Involvement I...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, selenium can inhibit autophagy by modulating the PI3K/AKT/mTOR signaling pathway, effectively preventing BBB injury following CIRI, particularly under hyperglycemic conditions. [55] Curcumin, [56] Cornin, [57] and Cyclo-(Phe-Tyr) [58] also inhibit excessive autophagy through this pathway to offer neuroprotection and maintain BBB integrity. Additionally, (-)-Epigallocatechin-3-gallate (EGCG), a bioactive component found in green tea, can inhibit autophagy via the AKT/AMPK/mTOR phosphorylation pathway, thus preventing further reperfusion injury in the mouse brain.…”
Section: Relationship Between Autophagy and Neurovascular Protection ...mentioning
confidence: 99%